Home is where the heArt is - Stigter, Diana; van Loon, Philippa; Museum van Loon, Amsterdam (Amsterdam : Museum van Loon, 2000)
Ackermann, Franz ; Atelier van Lieshout ; Berchem, Otto ; Cattelan, Maurizio ; Creed, Martin ; Eisinga, Jeroen ; Katzir, Ram ; Koelewijn, Job ; McQueen, Steve ; Wright, Richard ; Zwakman, Edwin
Museum van Loon, Amsterdam, November 3rd 2000 - January 7 2001
kunstcatalogus